E-035 Superior Outcomes in Thrombectomy for Anterior Circulation Large Vessel Occlusion Stroke among Late MR-Selected Candidates Compared with Early Candidates Not Screened with MR. (29th July 2016) - Cristiano, B; Pond, M; Oyoyo, U; Basu, S; Jacobson, J
Abstract : Purpose: With thrombectomy for anterior circulation large vessel occlusion (ACLVO) stroke time is considered important, but collateral status may be a greater driver of outcome than time. MR screening can identify good candidates for thrombectomy regardless of time from onset. Here we tested the hypothesis that MR-selected patients would show superior outcomes regardless of time compared with early patients screened by CTA alone. Methods: A cohort of 56 ACLVO patients treated with thrombectomy between 11/1/2012 and 5/15/2015 was retrospectively studied. Seven early-presenting patients with contraindication to MRI proceeded immediately to thrombectomy upon CTA confirmation of LVO. Forty-nine patients with CTA-proven LVO but no MR contraindication went next to MRI and were selected for thrombectomy based on low diffusion-restricted infarct volume (non-intervention threshold: core volume > (100 minus patient age) mL). Final infarct volume was measured on post-treatment imaging. Comparisons were made between early CTA-only-screened and MR-screened groups. Additional comparisons were made with the late MR-screened (decision-to-treat >6 hours from symptom onset) subset. Results: Compared to the MR-screened group, the early CTA-only group had a higher median age (81 [IQR 76–83] vs. 71 [57–77]) and NIHSS score (25 [22–26] v. 15 [11–19]) was more likely to have received IV tPA (71.4% vs. 36.7%) and yielded a lower TICI ≥ 2 B recanalization rate (57.1% vs. 79.6%, p = 0.36). Despite significantly earlier treatment decision times (3.0 h [2.5–3.6] vs. 6.4 h [2.9–8.7]), median final infarct volume was larger in the early CTA-only group compared with the MR-selected group (134 mL vs. 20 mL, estimated median final infarct difference of 100 mL [95 CI: 1.00–134], p = 0.043). A similar difference in median final infarct volume was observed between CTA-only and the late MR-screened groups (134 mL v. 27 mL [95 CI: –6 – 132], p = 0.069) (Figure 1 ). The odds of a final core infarct greater than 70 mL, a poor prognostic factor, were significantly lower in the MR-screened group OR 0.013 ([95 CI: 0.022–0.757], p = 0.022). Conclusion: Despite a median 3.4 hour-shorter interval from symptom onset to treatment decision, ACLVO patients not screened with MRI had larger median final infarct volumes after thrombectomy compared with MR-screened patients. Importantly, late MR-selected patients also tended to have lower final infarct volumes. Consideration should be given to patient selection strategies incorporating MRI with diffusion weighted sequences rather than time from symptom onset alone. Disclosures: B. Cristiano: None. M. Pond: None. U. Oyoyo: None. S. Basu: None. J. Jacobson: 4; C; GeneLux.